Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2466242
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation and transition

Abstract: People worldwide are increasingly acquiring collections of virtual possessions. While virtual possessions have become ubiquitous, little work exists on how people value and form attachments to these things. To investigate, we conducted a study with 48 young adults from South Korea, Spain and the United States. The study probed on participants' perceived value of their virtual possessions as compared to their material things, and the comparative similarities and differences across cultures. Findings show that y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…20% of those adults aged 65-75 used a smartphone (up from 12% in 2012). Survey data also reveals 49% of Internet users aged 55-64 had a social media profile, as did 28% of those aged 65+ [45]. These statistics broadly demonstrate the importance for HCI researchers to attend to the needs of ageing populations of online technology users [11].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…20% of those adults aged 65-75 used a smartphone (up from 12% in 2012). Survey data also reveals 49% of Internet users aged 55-64 had a social media profile, as did 28% of those aged 65+ [45]. These statistics broadly demonstrate the importance for HCI researchers to attend to the needs of ageing populations of online technology users [11].…”
Section: Introductionmentioning
confidence: 85%
“…Alongside a multi-generational perspective that considers the long-term sustainability of technology [18], it is argued there is great potential in studying key transition periods in a lifespan to critically consider our changing digital behaviors and values held in Internet-enabled technologies [2]. Therefore, HCI research has recently considered key events in technology users' lives, such as 'coming of age' [45,61], marriage [36], becoming a parent [22], relationship break-ups [57], divorce [40], and death and memorialization [37].…”
Section: Introductionmentioning
confidence: 99%
“…He contrasted them to personal physical possessions and proposed three distinctive qualities [Odom et al, 2014]: (i) placelessness -an absence of place where digital things can be found; (ii) spacelessness -they do not intrude into people's physical space and can thus grow invisibly; and (iii) formlessness -the fact that there is no clear sense of how virtual possessions can become unique personal artifacts. Furthermore, he argued that the accrual of metadata is another defining aspect of virtual possessions [Odom et al, 2011]: it allows for personalization, linking multiple types of virtual possessions together, and creating social stories [Odom et al, 2013].…”
Section: Studies Of Physical and Virtual Possessions In Interaction Dmentioning
confidence: 99%
“…Sharing virtual possessions in domestic environments comes with a number of challenges in comparison to their physical counterparts. Firstly, the virtual possessions are fragmented across different services (e.g., desktop, cloud storages, smartphones), which complicates users' sense of ownership [Odom et al, 2013] and control over them [Odom et al, 2012]. Secondly, a study of family heirlooms [Petrelli and Whittaker, 2010] revealed that digital belongings are often lacking symbolic associations and lasting value in comparison to their physical counterparts.…”
Section: Studies Of Physical and Virtual Possessions In Interaction Dmentioning
confidence: 99%
“…Such studies have included: insights into how home network technologies could support better user management [8]; understandings of the short lifetimes of mobile phones [9]; frameworks of personal attachment to inform the design of devices that are longer-lived and more likely to be cherished or passed on to others [10], [11]; reasons why electronic devices are kept even after they have fallen out of use [12]; how meaning is composed for digital data (messages, photo, video) compared to physical possessions [13]; how we might better support those who already devote significant effort and resources to reducing the impacts of their lives at home [14]; and how purchase, reuse and disposal of personal digital technology may relate to environmental concerns among young people [15].…”
Section: Introductionmentioning
confidence: 99%